Efficacy of lecture-based environmental education for biodiversity conservation: a robust controlled field experiment with recreational anglers engaged in self-organized fish stocking - Fujitani, Marie L.; McFall, Andrew; Randler, Christoph; Arlinghaus, Robert (Journal of applied ecology, 2016)
Fish stocking constitutes a widespread management tool for freshwater fisheries, but depending on configuration can be economically wasteful, ecologically harmful and lead to irreversible biodiversity loss. We conducted a large-scale controlled experiment of a lecture intervention to understand whether communication of neutrally worded scientific information about sustainable fish stocking might alter anglers’ ecological knowledge and cognitions (e.g. functional beliefs and attitudes) about the benefits and potential costs of fish stocking. Seventeen angler clubs from Germany who engage in self-organized fish stocking were randomly assigned to receive either a stocking lecture or a control lecture (on general fish management). From each club, self-selected anglers including water-body managers (N = 201) completed a questionnaire on ecological knowledge and cognitions about stocking before the lecture, immediately after the lecture and 10 months later to assess long-term retention. Data were analysed using Before-After-Control-Impact analysis with club-level random effects. Compared to the control group (n = 86), anglers in the treatment (n = 115) showed a significant post-lecture increase in knowledge in all six topics taught about the biological nuances of stocking and potential risks. However, there were no changes in stocking-related attitudes or personal norms towards future stocking. Only one knowledge domain was retained long-term (10 months): the understanding that stocking does not always have additive fishery effects (P < 0·05). There were also trends indicating long-term knowledge gains related to the genetic risks of stocking and the advantages of local adaptation, and a decreased functional belief in stocking efficacy (P < 0·08). These results suggest that participants may engage more cautiously in fish stocking in the future. Synthesis and applications. Lectures will continue to be a dominant mode of environmental education due to convenience and familiarity, particularly for stakeholders participating during leisure time and in contexts where training lectures are legally required. Our results show that lectures can effectively communicate complex ecological topics and lead to knowledge gain. Lectures on natural resource management will be most effective when addressing issues of high relevance to stakeholder's interests and modifying current practices, but changes in basic cognitions may require a more active learning environment.
Gesehen am 27.04.2020
First published: 23 October 2015